Developing Teacher's Professionalism To Improve the Quality of Education in Remote Areas - Meili Kurniati; Yasir Arafat; Mulyadi Mulyadi (INTERNATIONAL JOURNAL OF EDUCATIONAL REVIEW, 2020)
This study aimed at determining the efforts to develop elementary school teacher’s professionalism in remote areas and the factors that become obstacles faced by teachers to improve the quality of elementary school education. This research was carried out in and SD Negeri 16 and 31 Pulau Rimau. This research is descriptive qualitative. Data were collected using documentation, interviews, observation and literature review. Data were analysed using data collection, data reduction, presentation, and drawing conclusions and verification. The results stated that the development of professionalism of remote regional teachers in Banyuasin was 1) facilitating permission for elementary school teachers to continue their studies; 2) emphasizing school principals and teachers who have more ability to share abilities with peers; 3) reviewing each teacher after completing various training activities; 4) improve school facilities and infrastructure; 6) providing assistance to teachers who are implementing education; and 7) increasing the competency of school supervisors.